A comparison between hydraulic and pneumatic rockdrills - D. Clement (The Southern African Institute of Mining and Metallurgy, 1975)
A comparison between hydraulic and pneumatic rockdrills by D. CLEMENT The regulation of compressed-air reticulation systems is very poor compared with that of electrical systems; this means that electrohydraulic rockdrill systems offer greater flexibility, additional power being readily available at the working face. Hydrometallurgy A new journal devoted to all aspects of the aqueous processing of metals is scheduled to appear this year. Entitled Hydrometallurgy, the journal will be published in quarterly issues, one volume per year. Mineral dressing Contributions are invited for the Symposium on Recent Progress in Mineral Dressing in South Africa, which is to be arranged jointly by the South African Institute of Mining and Metallurgy and the National Institute for Metallurgy. Mineraalbereiding Bydraes word verlang tot die Simposium oor Onlangse Vordering met Mineraalbereiding in Suid-Afrika wat gesamentlik deur die Suid- Afrikaanse Instituut vir Mynbou en Metallurgie en die Nasionale Instituut vir Metallurgie gereel gaan word. Rock mechanics The Sixteenth Symposium on Rock Mechanics is to be held at the University of Minnesota from 22nd to 24th September, 1975. The Symposium is the official Symposium for 1975 of the International Society for Rock Mechanics (I.S.R.M.), and the Council for I.S.R.M., consisting of members from 25 countries, will meet during the Symposium. Powder metallurgy The annual meeting on powder metallurgy organized by The Metals Society is this year to be held at the Stratford Hilton Hotel, Stratford-upon-Avon (the notification did not include the date of the meeting). Vacation School The South African Institute of Mining and Metallurgy has great pleasure in announcing its intention of holding a vacation school on the topic of electric-furnace melting. NIM reports Report no. 1681 The determination of sulphur and phosphorus in chromite. Report no. 1687 The viscosities and electrical conductivities of slags associated with the production of high-carbon ferromanganese alloys.